The effect of attitude, subjective norm and behavioral control on decision repurchase intention via intent (a study on services company PT. Global Insight Utama Bali area) - Prayoga, Rizky Fadilla; Setiawan, Margono; Rohman, Fatchur (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2018)
Analyze the effect of perceived behavioral control to the high repeat purchase decisions by consumers through intention. The sample of 140 respondents. Mechanical analysis using SEM-PLS. The analysis shows that attitudes, subjective norms and behavioral control affect the intention. Attitudes, subjective norms and behavioral control influence on purchase decisions. Intention influence on purchase decisions. Attitudes, subjective norms and behavioral control influence on purchase decisions via Intent. subjective norms and behavioral control influence on purchase decisions. Intention influence on purchase decisions. Attitudes, subjective norms and behavioral control influence on purchase decisions via Intent. subjective norms and behavioral control influence on purchase decisions. Intention influence on purchase decisions. Attitudes, subjective norms and behavioral control influence on purchase decisions via Intent.